Overcoming barriers: A regulatory framework for Islamic open finance - Nisa Mutiara (Journal of Innovation in Business and Economics, 2025)
This study proposes a regulation-based solution to address the challenges of implementing Islamic Open Finance, focusing on Indonesia, which has the largest Muslim population yet a relatively low market share in Islamic finance. Using metadata analysis from the Scopus database, this study applies text mining and Natural Language Processing (NLP) to identify key challenges in the implementation of Islamic Open Finance. The findings highlight three critical areas from a regulatory perspective necessary for successful adoption; integrated data management standards, enhanced cybersecurity, and cultural shifts within institutions. Additionally, the study underscores the need to prioritize sharia-based financial literacy and education to foster acceptance within the community and the financial sector. This study recommends establishing a data protocol standard developed by the regulator, implementing a zero-trust cybersecurity model, and promoting cross-sector collaboration through regulatory forums.